2021
DOI: 10.1088/1757-899x/1077/1/012038
|View full text |Cite
|
Sign up to set email alerts
|

Image Captioning with Attention for Smart Local Tourism using EfficientNet

Abstract: Smart systems have been massively developed to help humans in various tasks. Deep Learning technologies push even further in creating accurate assistant systems due to the explosion of data lakes. One of the smart system tasks is disseminating ‘users needed information’, which is crucial in the tourism sector to promote local tourism destinations. In this research, we design a local tourism specific image captioning model, which will later support the development of AI-powered systems that assist various users… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…To produce the next word, adaptive attention [34] was used to determine when and at which part of the image should be focused on by using translated Microsoft Common Objects in Context (MS COCO) and Flickr30k datasets. Research [35] applied visual attention mechanism to their model to produce a caption for the image that makes greater sense. As the result, their model was able to give a sensible and detailed caption in the local tourism domain.…”
Section: Attention Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…To produce the next word, adaptive attention [34] was used to determine when and at which part of the image should be focused on by using translated Microsoft Common Objects in Context (MS COCO) and Flickr30k datasets. Research [35] applied visual attention mechanism to their model to produce a caption for the image that makes greater sense. As the result, their model was able to give a sensible and detailed caption in the local tourism domain.…”
Section: Attention Mechanismmentioning
confidence: 99%
“…Study with a specific domain, requires a specially made dataset because it has not been available before. Research [35] collected a total of 1,696 local tourism-related images from Google search engines.…”
Section: Indonesian Datasetsmentioning
confidence: 99%
“…However, during its development, the existing modeling was also trained on other datasets for more specific captioning tasks. The study [56] uses a dataset of images related to local tourism in Yogyakarta gathered from the Google search engine. This research aims to create a unique image captioning model for Yogyakarta tourism that can be expanded into a chatbot system.…”
Section: Introductionmentioning
confidence: 99%
“…We can find Image Captioning research in the Indonesian language using the existing dataset in research [12]- [15]. Meanwhile, Dhomas Hatta Fudholi conducted research for more specific applications, namely for local tourism image captioning [16] and household environment visual understanding [17], [18]. These studies were evaluated with several methods and showed that their evaluation scores were still low.…”
Section: Introductionmentioning
confidence: 99%